2019
DOI: 10.5397/cise.2019.22.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Focal Bone Marrow Lesions: A Complication of Ultrasound Diathermy

Abstract: Ultrasound diathermy is widely used for the treatment of musculoskeletal disorders and other soft tissue injuries. Its use as a therapeutic modality is believed to be safe, with very few reported complications. Here, we report two patients who developed focal bone marrow abnormalities after receiving ultrasound diathermy. Both patients’ magnetic resonance (MR) evaluations revealed linear subchondral bone lesions of the superolateral humeral head similar to those in osteonecrosis. The patients’ symptoms subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In the same way, in their two patients treated with US, Seung Jae J. Kim et al described diathermy-associated focal bone marrow abnormalities of the superolateral humeral head [ 64 ]. They concluded that the timing and transient nature of the findings in relation to the diathermy procedures suggest that US diathermy was the cause of these focal bone marrow lesions.…”
Section: Discussionmentioning
confidence: 97%
“…In the same way, in their two patients treated with US, Seung Jae J. Kim et al described diathermy-associated focal bone marrow abnormalities of the superolateral humeral head [ 64 ]. They concluded that the timing and transient nature of the findings in relation to the diathermy procedures suggest that US diathermy was the cause of these focal bone marrow lesions.…”
Section: Discussionmentioning
confidence: 97%